Russia’s power market reforms at the crossroads - Beyer, S (Oxford Institute for Energy Studies, 2014)
A decade of efforts were made to reform and liberalize the Russian electricity sector, with the unbundling of electricity networks and generation, the creation of an institutional governance framework and a wholesale electricity market, together with the privatization of generation assets. These changes attracted national and foreign investment into new generation capacity. In 2013, the government decided to launch a process to reform the Russian electricity market; this was planned to last until 2015. In 2014, discussions were still taking place over the ideal market design. Looking ahead, this reform is crucial for the modernization of the power sector, notably for the renewal of Russia’s large fleet of thermal power plants which were built 50 to 70 years ago. Up to 2035, around 80 per cent of nuclear capacity will reach the end of its lifetime and 78 per cent of hydropower plants will be in need of refurbishment. The IEA World Energy Investment Outlook 2014 estimates that the electricity sector in Russia will require investment of $411 billion in generation and $202 billion in networks by 2035.